Toxic Effect Induced by Cadmium on Some Reproductive Parameters and the Therapeutic Role of Leaves of Lemon Verbena - Salaho, Mohammad Amer; Kassem, Mahmoud (Journal of agricultural, environmental and veterinary sciences, 2021)
This study was conducted on 28 male Syrian hamsters, and the aim was to confirm the toxic effects of cadmium on the structure and function of the male reproductive system and to test the effectiveness of the alcoholic extract of the lemon verbena plant in the therapeutic of cadmium toxicity. The results of the study showed the negative effect of cadmium on some reproductive parameters of male Syrian Hamster, where treatment with cadmium (5mg/kg/day) reduced GSI% values ​​for both testis and epididymis, lowered the values ​​of testicular dimensions, testosterone concentration and some physiological parameters of the tail of the epididymis sperm and some histological measurements for testes, numbers of spermatogenesis cells, Sertoli and Leydig, cadmium treatment caused histological disorders in the testicles, compared to the control group. Dosing male hamsters with lemon verbena leaf extract at two concentrations (250,500mg/kg/day) did not lead to a clear improvement compared to the cadmium group.